Патріотична домінанта мотиву боротьби в поезії М. Вороного й Т. Шевченка - Шевель, Тамара; Shevel, Tamara (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті досліджено патріотичне звучання мотиву боротьби в поезії М. Вороного як прояв зацікавленості модерністів творчістю Т. Шевченка. Виявлено підтвердження цієї надуваги до постаті поета у творчому доробку М. Вороного, проаналізовано суголосність мотиву боротьби в поезії модерніста Шевченковому прагненню боротьби за волю. The article investigates the patriotic sound of the motif of struggle in the poetry of M. Voronyi as a manifestation of the interest of the modernist works of T. Shevchenko. It is noted that the poet was for the poet a benchmark attitudes and public purpose, namely Shevchenko notes of patriotism expressive sound in most poems of the cycle «Waves of struggle». Found confirmation of this attention to the personality of the poet in the works of M. Voronyi analyzed the affinity of the motif of struggle in the poetry of the modernist desire Shevchenko to the fight for freedom, found situational intertextuality and typological similarities. Noted a similar interpretation of the poets historical themes as an example of heroism and valor, but in the works. Black history speaks out updated and pereosmyslenie. Initial satirical note, in tune with the satire of T. Shevchenko. Nationalism meets the aspirations of early modernism to the emancipation of individuality, so the symbolism of poetry M. Voronyi is a notably expressive the motive of struggle in Shevchenko.
Patriotic Dominant Motif of Struggle in the Poetry of M. Voronyi and T. Shevchenko
Keywords: модернізм; символізм; національно-патріотичні мотиви; поетичний цикл; інтертекстуальність; modernism; symbolism; national and patriotic motives; poetic cycle; intertextuality